2017
DOI: 10.1111/zsc.12247
|View full text |Cite
|
Sign up to set email alerts
|

Rapid recovery of nuclear and mitochondrial genes by genome skimming from Northern Hemisphere freshwater crayfish

Abstract: 2017). Rapid recovery of nuclear and mitochondrial genes by genome skimming from Northern Hemisphere freshwater crayfish. -Zoologica Scripta, 46, 718-728. Molecular phylogenetics has benefited tremendously from the advent of next-generation sequencing, enabling quick and cost-effective recovery of whole mitogenomes via an approach referred to as 'genome skimming'. Recently, genome skimming has been utilised to recover highly repetitive nuclear genes such as 18S and 28S ribosomal RNA genes that are useful for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 68 publications
3
63
0
Order By: Relevance
“…New techniques may facilitate the retrieval of more complete mitochondrial (van der Valk et al, 2017) and nuclear data (e.g. Grandjean et al, 2017) from museum specimens.…”
Section: Discussionmentioning
confidence: 99%
“…New techniques may facilitate the retrieval of more complete mitochondrial (van der Valk et al, 2017) and nuclear data (e.g. Grandjean et al, 2017) from museum specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Studies based on morphology (cf. Braband, Kawai, & Scholtz, ; Kawai, ) are consistent in that the two general Holarctic branches (ie, the European astacids with American Pacifastacus and the American cambarids together with the East Asiatic Cambaroides ) form sister monophyletic assemblages, and subsequent molecular studies (Braband et al, ; Bracken‐Grissom et al, ; Breinholt, Perez‐Losada, & Crandall, ; Crandall, ; Grandjean et al, ; Owen et al, ) have instead shown a wide variety of relationships among these four key taxa.…”
Section: Discussionmentioning
confidence: 81%
“…Similar results were revealed in molecular studies by Ahn et al (), Johnson, Elder Jr., Thompson, Hightower, and Bechler (), and Owen et al (). Recent molecular phylogenies (Crandall & De Grave, ; Grandjean et al, ) based on extensive genetic sampling have confirmed that Cambaroides is the most basally separated Holarctic taxon, and the American cambarids are sister to the clade of European and American astacids. Based on not only own molecular analysis but also morphological distinctions and geographic affiliations, Crandall and De Grave () established for the genus Cambaroides the third Holarctic crayfish family, Cambaroididae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high abundance of 252 mitochondrial organelle in an actively dividing cell, the depth of mitochondrial-derived 253 sequencing reads will be substantially higher than that of the nuclear genome. While this 254 genomic feature has been used to rapidly recover complete mitogenome via the genome 255 skimming approach (Gan et al 2014;Grandjean et al 2017), overly high read depth of 256 the mitogenome obtained from a full genome sequencing data is likely to be detrimental 257 to de novo assembly due to the accumulation of sequencing errors, leading to the 258 generation of fragmented and/or incomplete mitogenome assembly (Mirebrahim et al 259 2015). In this work, we demonstrate that a simple subsampling approach followed by de 260 novo assembly could be an effective way to recover complete mitogenome from fungal 261 genome sequencing data.…”
Section: Mucilaginosa Rit389 247mentioning
confidence: 99%